PENGEMBANGAN MEDIA PEMBELAJARAN TEKS NEGOSIASI BERBANTUAN VIDEO POWTOON UNTUK SISWA KELAS X SMA - Mey Riska Putri; Ali Ali; Deliani Deliani (Jurnal Bahastra, 2022)
This study aimed to describe the development process and feasibility of negotiation text learning media assisted by Powtoon video for class X SMA students. The source of data is questionnaires. The type of data used quantitative descriptive data as the main data collected through an instrument with a Likert scale. Respondents in this study were material and media experts. The research method used 4-D of Research and Development by Thiagajangan that consists of 4 stages, namely Define, Design, Development, and Dissemination. This study is limited to the development and validation stages by four expert validators, since the current situation of Covid-19 so it cannot do the dissemination stage. Based on the results of the material expert responses, the overall material aspect average was 75% with the "Eligible" category. Meanwhile, media/design experts obtained an average overall aspect of 87% in the "Very Eligible" category. It means that the learning media is feasible and valid to be applied to small groups and large groups.